Enhanced production of polysaccharides and triterpenoids in Ganoderma lucidum fruit bodies on induction with signal transduction during the fruiting stage - Ye, Liyun; Liu, Shengrong; Xie, Fan; Zhao, Lili; Wu, Xiaoping (PloS one, 2018)
Ganoderma lucidum is a medicinal mushroom that has been widely used in East Asia for the treatment of various diseases. The pharmacological activity of this fungus is primarily attributable to the polysaccharides and triterpenoids. In this study, to obtain the fruit bodies with improved content of active constituents, we examined the effect of salicylic acid (SA) and calcium ion on the biosynthesis of polysaccharides and triterpenoids by spraying the chemicals during the fruiting. To explore the underlying mechanisms for the variation, the transcripts of related genes involved in the polysaccharide and triterpenoid biosynthesis were measured. Results showed that Ca2+ had no effect on production of polysaccharides and triterpenoids, whereas SA increased triterpenoid content by 23.32%, compared to the control, but it had little influence on polysaccharide production. Interestingly, the combined induction increased polysaccharide and triterpenoid content by 9.02% and 13.61%, respectively, compared to the control. Under Ca2+ induction, the transcript of ugp gene in the polysaccharide biosynthetic pathway up-regulated in all three stages (mycelium, primordium, and fruit body), while pgm and gls gave no response in the mycelium and primordium stages, and up-regulated in the fruit body stage. Differently, six key triterpenoid biosynthetic genes including hmgr, hmgs, mvd, fps, sqs, and ls did not respond to the induction. In the case of SA and combined induction, pgm and ugp were up-regulated in all three stages, while gls showed an increased expression in the primordium stage and no response in other stages. The six triterpenoid biosynthetic genes were up-regulated in all three stages. The present study provides a useful approach to producing G. lucidum fruit bodies with high polysaccharide and triterpenoid content. This is important to the G. lucidum industry.